Exosome-based miRNA delivery: Transforming cancer treatment with mesenchymal stem cells - Ashok Kumar Balaraman; M. Arockia Babu; Muhammad Afzal; Gaurav Sanghvi; Rekha M M; Sofia Gupta; Mohit Rana; Haider Ali; Kavita Goyal; Vetriselvan Subramaniyan; Ling Shing Wong; Vinoth Kumarasamy (Regenerative Therapy)
Recently, increasing interest has been in utilizing mesenchymal stem cell-derived extracellular vesicles (MSC-EVs), especially exosomes, as nanocarriers for miRNA delivery in cancer treatment. Due to such characteristics, nanocarriers are specific: biocompatible, low immunogenicity, and capable of spontaneous tumor accumulation. MSC-EVs were loaded with therapeutic miRNAs and minimized their susceptibility to degradation by protecting the miRNA from accessibility to degrading enzymes and providing targeted delivery of the miRNAs to the tumor cells to modulate oncogenic pathways. In vitro and in vivo experiments suggest that MSC-EVs loaded with miRNAs may inhibit tumor growth, prevent metastasis, and increase the effectiveness of chemotherapy and radiotherapy. However, these improvements present difficulties such as isolation, scalability, and stability of delivered miRNA during storage.Furthermore, the issues related to off-target effects, as well as immunogenicity, can be a focus. The mechanisms of miRNA loading into MSC-EVs, as well as their targeting efficiency and therapeutic potential, can be outlined in this manuscript. For the final part of the manuscript, the current advances in MSC-EV engineering and potential strategies for clinical application have been described. The findings of MSC-EVs imply that they present MSC-EVs as a second-generation tool for precise oncology.